La Subjetividad en la Tipificación del delito de Femicidio - Astudillo Quichimbo, Maria de los Angeles (2018)
The present investigation aims analysis to femicide, because few are the characteristics that determine as a constituents elements to this offence in article 141 of organic comprehensive criminal code (COIP) to determine the criminal type, in addition to Therefore the mess that exists in the Art 141 and the Art142 of the COIP, regards the constituent and the aggravating circumstances, these are the background that make my work to focus on this, and at the same time to legally recognize gaps in this pen type post not taken into account important factors and which are of great relevance at the time of sanction this behaviour, and in terms of judgements prevent subjectivities. Facing this reality that we are living and the fact that this crime has now its own typing, does not exempt that we must take necessary and immediate actions to establish better and provide a solution to this problem. For the fulfilment of the objectives of this research work I proceeded to analyze legal, doctrinal, and theoretical, where I could determine constituent elements so that you can configure a femicide and thus be able to a study of comparative law with laws such as Mexico, Colombia and Nicaragua, to demonstrate the violation of the right to legal certainty established by the Constitution. For the Foundation I basé on standards such as: first the Constitution of Ecuador Republic, criminal laws of other countries, coming to establish that by absence of these constituent elements violated the right to legal security. 4Also perform field work based on surveys aimed at professionals of law such as; lawyers in free practice, teachers, criminal lawyers, expressing its point of view concerning the current situation on this offence. After this extensive research I can conclude declared that not exist precisely these fundamental characteristics for the configuration of this crime violated the right to legal security laid down in the Constitution of the Republic.